Targeted codelivery of nitric oxide and hydrogen sulfide for enhanced antithrombosis efficacy - Weiliang Deng; Zhixin Xu; Tong Hua; Guangbo Ji; Zihang Wang; Pei Liu; Yupeng Zhang; Shuo Li; Yuqiu Chao; Meng Qian; Qiang Zhao; Jinwei Tian (Bioactive Materials)
Thrombosis is a leading cause of mortality worldwide. As important gaseous signaling molecules, both nitric oxide (NO) and hydrogen sulfide (H2S) demonstrate antiplatelet and anticoagulant functions, but little attention has been given to their synergistic effect and the underlying mechanism. In the present study, we developed an NO/H2S codelivery system based on enzyme prodrug therapy (EPT) strategy in which the prodrugs are specifically recognized by the engineered β-galactosidase. Targeted codelivery of NO and H2S in vivo was demonstrated by near-infrared fluorescence imaging and confirmed by measuring plasma and tissue levels; as a result, the side effects caused by systemic delivery, such as bleeding time, were reduced. Delivery of an optimized combination of NO and H2S with a low combination index (CI) results in a synergistic effect on the inhibition of platelet adhesion and activation. Mechanistically, NO and H2S cooperatively enhance the cGMP level through redox-based posttranslational modifications of phosphodiesterase 5A (PDE5A), which leads to activation of the cGMP/PKG signaling pathway. Furthermore, targeted codelivery of NO and H2S demonstrates enhanced therapeutic efficacy for thrombosis in two mouse models of FeCl3-induced arterial thrombosis and deep vein thrombosis. Collectively, these results confirm the synergistic efficacy of NO and H2S for antithrombotic therapy, and the codelivery system developed in this study represents a promising candidate for clinical translation.